Digital Content Marketing as Business Strategy for Japanese Video Game Company in the Network Society - Abyan Nurfikri Muhammad; Kurniawaty Iskandar (LONTAR: Jurnal Ilmu Komunikasi, 2024)
This study examines how CapCom, a company in the Japanese video game industry, increased its sales through digital content marketing. Japan is one of the countries that has strength in the global economy in various aspects of the economy, one of which is the video game industry. The video game industry in Japan has gone through several periods ranging from the arcade era to the handheld era. CapCom is one of the Japanese companies engaged in the video game industry. The company focuses its business on digital content marketing. This is also CapCom's effort to increase its sales. This research uses Castells' theory of network society and Koiso and Kanttila's concept of digital content marketing with a leatherative research method and document analysis obtained from online sources. Based on the analysis of data collected from various sources, CapCom's effort to increase its sales through digital content marketing is by utilizing global networks for various marketing purposes. Then, CapCom also tends to emphasize value-added services by offering DLC (downloadable content) on its digital content to increase sales and consumer loyalty to the company.